role of density dependence in the population dynamics of a tropical palm - Silva Matos, D.M; Freckleton, R.P; Watkinson, A.R (Ecology (Durham), 1999)
The role of density dependence in the population dynamics of tropical trees has been a subject of considerable debate. Here, we present data on the demography of the edible palm Euterpe edulis, classified into seven size categories and monitored over three years. On average, each adult palm contributed 98 seedling recruits per year into the population. The pattern of mortality was similar to that of other palms, with mortality being highest among the smallest plants. Those plants with a diameter at soil level >20 mm had an annual mortality <7%. Density dependence was found to act only on the seedling stage of the life cycle. The probability of survival and transition of seedlings to the next size class were affected both by the density of seedlings and the presence of conspecific adults. Matrix modeling indicated that the true finite rate of population increase (λ ) was 1.28 and that the observed reverse "J"-shaped size distribution of plants was a consequence of the density dependence operating in the population. Elasticity analysis showed that the survival elements in the matrix contributed most to the value of λ , and that the position of the transition matrix in growth-survival-fecundity (G-L-F) space was influenced by density. The matrix model incorporating density dependence predicted size distributions and densities approximating the maximum observed in the field. Spatial simulations indicated that the predictions from the matrix model relating to the size structure of plants are robust, but that the predictions of densities are sensitive to the precise spatial dynamics of the population.